Assessing privacy and readiness of electronic voting system in Indonesia - Lubis, Muharman; Kartiwi, Mira; Durachman, Yusuf (IEEE, 2017)
Indonesia as one of the country that adopts democracy, it is required to conduct elections freely and fairly by meeting the principles of direct, general and secret. Meanwhile, the use of ICT in the term of e-voting promise the end results can be obtained quickly and real-time in the delivery and tabulation process. The implementation of e-voting in Indonesia has begun in Jembrana District for the election of village heads, followed by many simulations based on initiative from BPPT in various location. This paper introduces an up-to date and discuss clearcut solutions for multiple voting constraints and problem. It suggest some consideration to be taken care to prevent the majority of known problems with e-voting. Most importantly, the paper presents the recommendations which engage the citizen opinion and expert knowledge in the field to pinpoint the path to success in implementing e-voting in respect of political decision and economic challenges.